PCR in the investigation of canine American tegumentary leishmaniasis in northwestern Paraná State, Brazil - Velasquez Leonardo Garcia; Membrive Norberto; Membrive Umberto; Rodrigues Gesse; Reis Nélio; Lonardoni Maria Valdrinez Campana; Teodoro Ueslei; Tessmann Ione Parra Barbosa; Silveira Thaís Gomes Verzignassi (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2006)
American tegumentary leishmaniasis (ATL) was studied in 143 dogs in a rural area in the county of Mariluz, northwestern Paraná State, Brazil, using direct parasite search, indirect immunofluorescence (IIF), and polymerase chain reaction (PCR). Thirty-nine dogs (27.3%) presented lesions suggestive of the disease, 5 (12.8%) of which were positive in direct parasite search and PCR (lesion), and of these 5, 4 were also positive by IIF. Of the 34 dogs with negative direct parasite search, 12 (35.3%) had PCR- positive lesions, and of these, 5 were also IIF-positive. One hundred and four dogs had no lesions, but 17/101 (16.8%) were IIF-positive. PCR in blood was positive in 10/38 (26.3%) of the dogs with lesions and in 16/104 (15.4%) of dogs without lesions. The association between PCR (lesion or blood), direct parasite search, and IIF detected 24/39 (61.5%) positive results among symptomatic dogs and 31/104 (29.8%) among asymptomatic animals. PCR was useful for diagnosing ATL, but there was no correlation between lesions, serology, and plasma PCR. Furthermore, detection of parasite DNA in the blood may indicate hematogenous parasite dissemination.